2020
DOI: 10.1109/tmi.2019.2963177
|View full text |Cite
|
Sign up to set email alerts
|

3D-GLCM CNN: A 3-Dimensional Gray-Level Co-Occurrence Matrix-Based CNN Model for Polyp Classification via CT Colonography

Abstract: Accurately classifying colorectal polyps, or differentiating malignant from benign ones, has a significant clinical impact on early detection and identifying optimal treatment of colorectal cancer. Convolution neural network (CNN) has shown great potential in recognizing different objects (e.g. human faces) from multiple slice (or color) images, a task similar to the polyp differentiation, given a large learning database. This study explores the potential of CNN learning from multiple slice (or feature

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 48 publications
(70 reference statements)
0
49
0
Order By: Relevance
“…Sum variance can be defined as an indirect parameter of gray level textural dispersion around the mean. For details on the precise mathematical algorithm for the calculation of textural features, the reader is referred to previous publications (Ou et al, 2014; Mapayi et al, 2015; Tan et al, 2016, 2020; Dincic et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Sum variance can be defined as an indirect parameter of gray level textural dispersion around the mean. For details on the precise mathematical algorithm for the calculation of textural features, the reader is referred to previous publications (Ou et al, 2014; Mapayi et al, 2015; Tan et al, 2016, 2020; Dincic et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The combination of ANNs and CT has also been used in the diagnosis of cancer metastasis and invasion depth[ 53 - 56 ], which are also important indicators of patient prognosis. A study even reported that CNN-based systems could distinguish benign and malignant lesions by CT[ 57 ]. More possible development directions of CT were discussed.…”
Section: Achievements Of Ann Research In Gi Diseasesmentioning
confidence: 99%
“…This approach takes longer time with 12000 iterations which make it more complex and time consuming as well as using larger dataset. The CNN model has been implemented [5] with Gray Level Co-occurrence Matrix(GLCM) [44] to assists the Computer Aided Diagnoses (CADx) [45] system for the classification of all types of medical images like MRI and CT. The proposed method was used to extract and convert the information of irregular segmentation regions of the image into fixed-size GLCM input for CNN.…”
Section: Related Workmentioning
confidence: 99%